The use of geotechnologies in the analysis of irrigated areas of Córrego da Conserva watershed in Vargem Grande do Sul, SP: An agroecological approach (Research, Society and Development, 2022)
The present study aims to characterize the land use and occupation of the Córrego da Conserva Basin in Vargem Grande do Sul - SP. The mapping was performed using the free software QGIS to study the area and it enabled the pursuit of sustainability. The classes obtained were: nascent, water bodies, water courses, central pivot, built area, sugarcane, citrus, pasture, native vegetation and the Permanent Preservation Areas (APPs). The results obtained highlight the small proportion of 4.18% of native vegetation present in the study area. The occupied territory shows an intensive use of water in the irrigation of conventional agriculture, with the technique of central pivot, thus evidencing conflict in water use. Thus, it is necessary to plan the use an occupation of the land, in the search for sustainability with an agroecological focus. In this sense, it should be emphasized the importance of adequate land management and irrigation, in order to collaborate for the planning of the area and thus support local public policies.